A School-based Management and Supervision Model in EFL Schools - Nurhuda. H Nurhuda. H (ELT-Lectura, 2014)
This article offers a school-based reflective management model in EFL schools that centers on reflective practice for EFL teachers and administrators drawing on four bodies of literature (reflective thinking, supervision, teacher inquiry in EFL context and organizational learning). This study introduce "reflective management and supervision" and the terms "management" and "supervision" are used interchangeably to describe the broadest contexts in which this study advance the concept of the teacher and administrator as both reflective practitioner and instructional leader and take school administrator as a "non-managerial" "consultative" curriculum developer/supervisor, and head learner.